Rhodanine derivative LJ001 inhibits TGEV and PDCoV replication in vitro - Zhang, Yunfei (Virus Res, 2020)
Transmissible gastroenteritis virus (TGEV) and porcine deltacoronavirus (PDCoV) are members of the family coronaviridae and mainly cause acute diarrhea/vomiting, dehydration and mortality in piglets, which lead to huge economic losses to the swine industry. Rhodanine derivative LJ001 has been verified to be effective against some enveloped virus infections in vitro. In this study, we evaluated the antiviral activity of LJ001 towards TGEV and PDCoV replication on swine testicular(ST) cells. Our results showed the 50 % cellular cytotoxicity (CC(50)) value of LJ001 was 146.4 μM on ST cell. The virus titers of TGEV and PDCoV were obviously decreased in the presence of LJ001 with the concentrations of 3.125 and 12.5 μM, and LJ001 potently inhibited TGEV and PDCoV infection at the replication stages of viral life cycle. Further study indicated that LJ001 inhibited TGEV and PDCoV replication by inhibition of viral RNA and protein synthesis, and reducing virus yields at 12 and 24 h post-inoculation. These data indicated that LJ001 had antiviral activities on TGEV and PDCoV replications in vitro, which may serve as a new candidate for treatment of coronaviruses infections.